Dissecting Aneurysm of the Anterior Cerebral Artery Presenting with Thrombo-Embolic Complications: A Case Report - Hofman, P.A.M. (Centauro S.r.l., 2004)
A dissecting aneurysm of the anterior cerebral artery is a relatively rare disorder. A patient is presented with mild symptoms due to thromboembolic complications from a dissecting aneurysm of the pericallosal artery. The patient had a good outcome after conservative treatment. A review of the literature is presented.